Factors associated with dental caries in children with bronchial asthma aged 24 to 71 months, Lima, Peru - Acosta Montoya , Milagritos Claudia (2025)
Objectives: To determine the factors associated with dental caries in preschool children with bronchial asthma. Materials and Methods: The methodological design of this study was observational, retrospective and cross-sectional. The sample consisted of clinical records of preschool children aged 24 to 71 months, treated at the "Todos los Santos San Borja" Health Center in the district of San Borja, with a diagnosis of bronchial asthma, between 2015 and 2016. The ceo-d index was used to assess the presence of dental caries. Results: A relationship was found between the dental caries index and the number of asthma episodes per year (p=0.044), as well as with the sociodemographic factor age (p=0.020). No significant relationship was found between the dental caries index and brushing frequency (p=0.361), factors related to asthma condition p=0.349, time since diagnosis (p=0.25), duration of medication use (p=0.46), or asthma severity (p=0.567). No relation was observed with sex, parental education level, or household income. Conclusions: The study determined that factors associated with dental caries in children with bronchial asthma include the number of asthma episodes per year and the child´s age.